1991
DOI: 10.1152/ajprenal.1991.260.6.f883
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of sodium retention in heart failure: relation to the renin-angiotensin-aldosterone system

Abstract: Renal plasma flow (RPF), glomerular filtration rate (GFR), renal proximal tubular delivery of sodium and water evaluated by lithium clearance, and hormonal parameters were measured in 12 patients with congestive heart failure NYHA class II-IV before and after captopril treatment for 4 wk and in 13 healthy control subjects. RPF and GFR were significantly decreased in heart failure, whereas the filtration fraction (FF) was increased. Treatment with captopril increased RPF and decreased FF, whereas GFR was unchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…UNx already represents a state of mild renal damage as the hemodynamic adaptations occur in the remaining glomeruli to compensate for the nephron loss. Several mechanisms by which MI accelerates mild renal damage may be hypothesized, including neurohumoral activation occurring after the MI and subsequent heart failure (8,9), the endothelial dysfunction of the systemic arteries (10,11), or the generalized inflammatory reaction that is associated with acute MI. Our data, however, indicate that the renal effects of MI depend, at least partially, on intrarenal factors that are present before the injury (MI) triggers renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…UNx already represents a state of mild renal damage as the hemodynamic adaptations occur in the remaining glomeruli to compensate for the nephron loss. Several mechanisms by which MI accelerates mild renal damage may be hypothesized, including neurohumoral activation occurring after the MI and subsequent heart failure (8,9), the endothelial dysfunction of the systemic arteries (10,11), or the generalized inflammatory reaction that is associated with acute MI. Our data, however, indicate that the renal effects of MI depend, at least partially, on intrarenal factors that are present before the injury (MI) triggers renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…53). Thus in HF activation of RAAS may become a maladaptive response to arterial underfilling, introducing a vicious cycle leading to increasing morbidity and mortality (17). As a consequence, a variety of pharmaceutical efforts have targeted the RAAS.…”
Section: /Hmentioning
confidence: 99%
“…Studies in HF patients and in experimentally induced rat models have revealed dysregulation of some of the renal sodium transporters indicating enhanced sodium reabsorption in the proximal tubule (59) and thick ascending limb (TAL) of Henle (17,55). After bulk transport in the proximal tubule and TAL, the distal nephron, including renal CNT and CD, is responsible for the final regulation of urinary sodium excretion.…”
Section: /Hmentioning
confidence: 99%
“…The mechanisms behind this impairment in sodium handling in mild CHF are not fully clarified, but it has been suggested that renal sodium retention in mild CHF is caused by an increase in proximal tubular sodium reabsorption (21,36). However, in another study using lithium clearance (C Li ) as a marker for delivery of fluid out of the proximal tubules, Eiskjaer and co-workers (9) showed that proximal tubular function was normal in patients with CHF and increased plasma levels of renin and aldosterone.…”
mentioning
confidence: 99%